Pidana Terhadap Pelaku Pengulangan (Residive) Tindak Pidana Peredaran Narkotika dalam Perspektif Hukum Penitensier - Nabila Oktavia Lestari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Narcotics are substances or drugs, whether synthetic or semi-synthetic, derived from plants or non-plant materials that have the potential to cause disturbances or changes in human consciousness. Their use may result in loss of sensation, impaired taste, and, in more severe cases, strong dependency or addiction. While narcotics have undeniable benefits in the fields of medicine, healthcare, and scientific development—particularly in pain management and research—their misuse carries significant risks for both individuals and society. This study adopts a normative legal approach by analyzing existing regulations, statutory provisions, and relevant academic literature regarding narcotics and crime. The findings reveal that narcotics abuse is often closely linked to criminal behavior, as drug dependence can negatively influence psychological stability, decision-making, and social conduct, potentially driving individuals to engage in unlawful acts. Furthermore, crime is a relative concept shaped by context, culture, and societal norms, which means its connection with narcotics requires multidimensional analysis. Law enforcement efforts against narcotics-related crimes have been continuously pursued by authorities through preventive, repressive, and judicial measures, with various court rulings highlighting the gravity of the problem. However, legal enforcement alone is insufficient; a holistic strategy is needed that combines strict law enforcement with rehabilitation, psychological support, and community education. Such a comprehensive approach is expected to reduce narcotics misuse, prevent recidivism, and minimize its destructive impacts. Ultimately, this research seeks to provide deeper insights into the dynamic relationship between narcotics abuse and crime, while offering practical recommendations to achieve more effective solutions for protecting individuals, strengthening social resilience, and promoting public welfare